Perspectives on Imaging the Left Main Coronary Artery Using Intravascular Ultrasound and Optical Coherence Tomography - Lowe, Harry C. (Frontiers in Cardiovascular Medicine, 2015)
Percutaneous Coronary Intervention (PCI) for significant left main coronary artery (LMCA) stenosis is increasingly being viewed as a viable alternative to Coronary Artery Bypass Grafting (CABG) (1). This is leading to an expectation of increasing numbers of such procedures, with a consequent focus on both the ability to image both lesion severity, and assess more accurately the results of PCI. While there have been advances in physiologic assessment of left main severity using fractional flow reserve (FFR), imaging of the LMCA using Intravascular Ultrasound (IVUS) and more recently Optical Coherence Tomography (OCT) has the specific advantage of being able to provide detailed anatomical information both pre and post PCI, such that it is timely to review briefly the current status of these two imaging technologies in the context of LMCA intervention.